Concluding Remarks: Kinship between Choice and Contestation - Ergas, Yasmine (Anthropologica, 2015)
The contributors to this thematic section show women and men negotiating reproduction and family relations in contexts marked by globalization, expanding commodification, assisted reproductive technologies (ARTs) and the assertion of women’s right to determine their child-bearing. These factors operate synchronically to produce new markets. New forms of "kin work" emerge as familial bonds are imaginatively established and sundered. Commodification and connection are uneasily balanced when globalization simultaneously fosters new modes of kin-making and facilitates their rupture.